Structural and mechanistic insights into mechanoactivation of focal adhesion kinase - Bauer, Magnus Sebastian; Baumann, Fabian; Daday, Csaba; Redondo, Pilar; Durner, Ellis; Jobst, Markus Andreas; Milles, Lukas Frederik; Mercadante, Davide; Pippig, Diana Angela; Gaub, Hermann Eduard; Gräter, Frauke; Lietha, Daniel (Proceedings of the National Academy of Sciences of the United States of America, 2019)
Focal adhesion kinase (FAK) is a key signaling molecule regulating cell adhesion, migration, and survival. FAK localizes into focal adhesion complexes formed at the cytoplasmic side of cell attachment to the ECM and is activated after force generation via actomyosin fibers attached to this complex. The mechanism of translating mechanical force into a biochemical signal is not understood, and it is not clear whether FAK is activated directly by force or downstream to the force signal. We use experimental and computational single-molecule force spectroscopy to probe the mechanical properties of FAK and examine whether force can trigger activation by inducing conformational changes in FAK. By comparison with an open and active mutant of FAK, we are able to assign mechanoactivation to an initial rupture event in the low-force range. This activation event occurs before FAK unfolding at forces within the native range in focal adhesions. We are also able to assign all subsequent peaks in the force landscape to partial unfolding of FAK modules. We show that binding of ATP stabilizes the kinase domain, thereby altering the unfolding hierarchy. Using all-atom molecular dynamics simulations, we identify intermediates along the unfolding pathway, which provide buffering to allow extension of FAK in focal adhesions without compromising functionality. Our findings strongly support that forces in focal adhesions applied to FAK via known interactions can induce conformational changes, which in turn, trigger focal adhesion signaling.